Stochastic Volterra Equation Driven by Wiener Process and Fractional Brownian Motion - Zhi Wang; Litan Yan (Abstract and Applied Analysis)
For a mixed stochastic Volterra equation driven by Wiener process and fractional Brownian motion with Hurst parameter H>1/2, we prove an existence and uniqueness result for this equation under suitable assumptions.